Pathogenetic significance and possibility as a therapeutic target of platelet derived growth factor. Issue 5 (10th April 2017) - Ishii, Yoko; Hamashima, Takeru; Yamamoto, Seiji; Sasahara, Masakiyo
Abstract : Platelet‐derived growth factor (PDGF) is one of the major mitogens and chemoattractants for mesenchymal and glial cells. Nowadays, the expression of PDGFs are recognized widely in our body, and emerging data indicate the relevance of PDGFs in the homeostatic control of systemic connective tissue as well as parenchymal cells such as neurons. Aberrant PDGF signal is primarily tumorigenic, and also regulates tumor microenvironments. The roles of the PDGF signal in tumorigenesis are diverse depending on the type of cancer, and anti‐PDGF therapy needs to be carefully designed based on the information of each tumor cell type and the surrounding microenvironment. PDGFs and receptors (PDGFRs) are abundant in neurons and glial cells, and are neuroprotective through the regulation of neurovascular unit. PDGF signal is functionally correlated with neurotransmission, and can be pathogenetically correlated with psychosomatic neurological diseases. Growing genetic information has been unraveling novel connective tissue diseases and vascular abnormalities in which aberrant PDGF signaling is etiologically correlated. Novel therapeutic approaches targeting PDGF signal are beginning to emerge in various diseases.